Distribution of wheat stem rust (Puccinia graminis f. sp. tritici) and its association with biophysical factors and cultivation practices in Horro Guduru Wollega highlands, Western Ethiopia - Abdissa, Tola; Fininsa, Chemeda; Abeyo, Bekele Geleta; Woldeab, Getaneh (Springer, 2024)
Wheat stem rust (Puccinia graminis f. sp. tritici) is the major threat to wheat production in Ethiopia due to the menace of high losses in grain yield and quality. A wheat stem rust survey was undertaken during the main cropping seasons (late October to early November) of 2015 and 2016 in the Horro Guduru Wollega highlands, western Ethiopia. The purposes of the survey were to assess the wheat stem rust distribution and disease intensity and determine its association with biophysical factors and cultivation practices. A total of 221 wheat fields in eight districts were assessed. Wheat stem rust was prevalent in both cropping seasons. The mean disease incidence ranged from 56.3 to 63.7%, while the disease severity mean ranged from 15.7 to 21.6%, respectively. Logistic regression was used to analyze the association of wheat stem rust with independent variables. Increased incidence (>50%) and severity (>5%) were strongly (P < 0.0001) associated with lower altitude (<= 2400 m), susceptible varieties, broadcast sowing method, fungicide-unsprayed wheat fields, and wheat growth at flowering and milking stages. The survey indicates a highly prevalent wheat stem rust epidemic associated with biophysical factors and cultivation practices in the major wheat-growing districts. A combination of cultivation practices such as sowing wheat in rows, optimum fertilization, deployment of rust-resistant varieties, and effective fungicide application would be the most effective methods for managing wheat stem rust in the Horro Guduru Wollega highlands.